Coach Expectations About Off-Field Conduct and Bystander Intervention by U.S. College Football Players to Prevent Inappropriate Sexual Behavior. Issue 2 (January 2018) - Kroshus, Emily; Paskus, Tom; Bell, Lydia
The objective of the present study was to assess whether there is a positive association between expectations about off-field conduct set by the team coach and the likelihood that college football players intend to engage as prosocial bystanders in the prevention of what they consider to be inappropriate sexual behavior. In a sample of U.S. collegiate football players ( N = 3, 281), a path analysis model tested the association between coach expectations, perceived likelihood of discipline for off-field transgressions, and likelihood of intending to intervene to prevent inappropriate sexual behavior. Mediation of these relationships by the athlete's sense of exploitative entitlement and their attitudes about intervening were also assessed. Findings supported the hypothesized relationships, with expectations and discipline associated with bystander intentions both directly and indirectly through the mediating pathways of entitlement and attitudes about intervening. These findings provide evidence about the important role that sports team coaches can play in encouraging bystander intervention by clarifying expectations and consequences for conduct off the field of play. Athletic departments can provide a framework within which coaches are informed about the importance of setting and enforcing standards for off-field behavior, and are appropriately incentivized to do so.